Exploration of Quantum Chemistry Methods to Explain Mechanism of Mechanochemical Degradation of Typical Organic Pollutants - Xiaohui Zhang; Xiaoqian Xu; Zeya Zhang; Liang Pei; Tongshun Han (Toxics)
The high-efficiency ball milling treatment technology primarily combines the excitation of oxidation processes with high-speed physical collisions, thereby promoting the reaction processes and enhancing the degradation effectiveness of materials. This technology has gained widespread attention in recent years for its application in the degradation of organic solid chemical pollutants. In this study, quantum chemical density functional theory (DFT) was employed to first analyze the impact of electron addition and subtraction on molecular chemical bonds. The molecular energies of the target pollutants and their possible intermediates were then calculated, and the theoretical energies required for the degradation pathways of the target organic compounds under oxidative-enhanced ball milling were computed. This further validated the accuracy of the ball milling experimental results. The theoretical energy required for the complete mineralization of solid organic chemicals through ball milling degradation was calculated, with values of 16,730.74 kJ/mol for lindane, 20,162.46 kJ/mol for tetrabromobisphenol A, 10,628.04 kJ/mol for sulfamethoxazole, and 4867.99 kJ/mol for trimethoprim. By combining different ball milling experimental conditions, the theoretical reaction time required for the complete mineralization of the target organic chemicals can be calculated. The comparison of theoretical calculations with the experimental results provides new insights into the ball milling degradation process and degradation pathways of the target pollutants.